Asthma phenotypes in a multi-ethnic Asian cohort. (October 2019) - Tay, Tunn Ren; Choo, Xue Ning; Yii, Anthony; Chung, Kian Fan; Chan, Yiong Huak; Wong, Hang Siang; Chan, Adrian; Tee, Augustine; Koh, Mariko S.
Abstract: Background: Identification of asthma phenotypes facilitates our understanding of asthma pathobiologies. Phenotypes observed in homogenous Asian cohorts have distinct differences from those described in Caucasian cohorts, suggesting that ethnicity may influence phenotypic expression. Phenotypic clusters in a multi-ethnic Southeast Asian cohort have not been described before, and direct comparisons of these clusters within a single study may reveal how ethnicity affects phenotypic expression. Methods: Six hundred and thirty adult asthma patients from two healthcare institutions in Singapore were randomly assigned in a 2:1 fashion to a test and validation cohort. Latent class analysis was performed on both cohorts using age of asthma onset, sex, ethnicity, smoking status, body mass index, lung function, blood eosinophil count, asthma control test score, and exacerbation frequency as input variables. Phenotypic clusters between the test and validation cohorts were compared Results: Three clusters were identified in both the test and validation cohorts, with corresponding clusters of each cohort sharing similar characteristics. Ethnic representation and asthma control were significantly different between clusters. Cluster one comprised Chinese females with late-onset asthma and the best asthma control. Cluster two comprised non-Chinese females with obesity and the worst asthma control. Cluster three was multi-ethnic with the greatest proportion of atopic patients. Conclusion: We identified three phenotypic clusters in our multi-ethnic Southeast Asian population, with distinct differences in ethnicity which may be attributable to inherent differences in baseline characteristics among ethnic groups. Highlights: We identified 3 distinct phenotypic clusters in patients with asthma in Singapore. Ethnic representation differed significantly between the clusters. The obese, female and non-Chinese cluster had the worst asthma control.